Factors determinate customer shopping behaviour through Internet: the Malaysian case - Haque, A. K. M. Ahasanul; Khatibi, Ali; Al Mahmud, Shameem (INSInet Publications, 2009)
This study try to explore factors that are affect shopping behaviour of the customer, how does Internet marketing affect the behaviour of the customer. Factor analysis is used in this study to identify the salient attributes that have impact on consumers’ shopping behaviour about Internet marketing. Since, Factor analysis represents an analytical process of transforming statistical data (as measurements) into linear combinations of variables. In addition, multiple regression model was estimated to anticipate the effects of the explanatory variables. Findings of regression analysis indicated that all four factors such as Internet marketing environment, product characteristics, familiarity and confidence and promotional offer have significant impact on customer intention about Internet marketing. In conclusion, underlying uncertainty of customers as to the security of transaction on the Internet. Customers may not yet be ready for the transactional purposes due to security concern and mentally afraid doing transaction online due to security reason. They believe that online transactions are not secured enough to protect the payment method as disclosure of information.